Perancangan Sistem Penjualan Berbasis Website Menggunakan Metode Rapid Application Development (Studi Kasus: Cafe Pojok Temu) - Laeli Rahma Dini; Demonius Sarumaha; Saiful Amir (CV. Shofanah Media Berkah, 2025)
The rapid development of information technology in the era of globalization has encouraged culinary business actors to utilize online-based systems as a medium for promotion and customer service. One of the main problems faced by restaurants is the limited use of digital promotion media and the inefficiency of conventional food ordering and reservation processes. This study aims to design and develop a web-based information system for promotion and food ordering to improve promotional effectiveness and reservation efficiency. The system development employs the Rapid Application Development (RAD) method, which consists of three main stages: planning, system design and development, and implementation. The developed information system provides several features, including restaurant profile information, menu and pricing details, restaurant location integrated with Google Maps, online ordering or reservation facilities, and sales reporting. The results indicate that the web-based information system is able to assist restaurant owners in managing promotions and orders more effectively, while also providing customers with easy access to information and online reservation services without direct face-to-face interaction. Therefore, the implementation of this system is expected to enhance service quality, time efficiency, and the competitiveness of restaurant businesses.